Motivational and Perception Changes in Learning Japanese in Brunei Darussalam - Akita, Yuki (Border Crossing, 2017)
This study explores issues related to motivation and perception change towards learning Japanese among language students at the Universiti Brunei Darussalam. The aim of this study is to 1) explore students’ motivational change during the semester, 2) identify the factors that influence these changes, and 3) ascertain any changes to students’ perceptions regarding the difficulty in acquiring Japanese language skills. The questionnaire survey was conducted at the beginning and at the end of a 14–week semester. Findings show that the major motivating factor identified was the teacher and the major demotivating factor was difficulty of the language. It was also found that while students perceived writing skills were the most difficult at the beginning of the semester, their perception about difficulty has shifted to listening skills at the end of the semester.